Implementasi Pembelajaran Kitab Syi’ir Ngudi Susilo dalam Membentuk Akhlak Santriwati terhadap Guru di Pondok Pesantren Al Qutub Wonopringgo Pekalongan - Ismasar, Ismasari; Prayogi, Arditya; Setiawan, Singgih; Nasrullah, Riki (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
Moral learning is a fundamental aspect in Islamic education, especially in Islamic boarding schools. This study aims to examine the implementation of learning the book Syi'ir Ngudi Susilo in shaping the morals of female students towards teachers at the Al Qutub Wonopringgo Pekalongan Islamic Boarding School. This book was chosen because of its relevant content in instilling the values ​​of akhlakul karimah and strengthening the manners of students towards teachers. The research method used was qualitative with data collection through observation, interviews, and documentation. Data analysis was carried out using data reduction, presentation, and verification techniques based on the Miles and Huberman interactive model. The results of the study showed that the dominant learning methods used were bandongan and memorization. The bandongan method allows female students to understand the contents of the book directly through the teacher's explanation, while the memorization method helps them internalize the teachings of the book. Although most female students showed an increase in morals towards teachers, there were still obstacles such as being unaccustomed to applying the values ​​taught, academic pressure from schools and boarding schools, and limited communication with teachers. This study confirms that moral education in Islamic boarding schools requires supporting strategies such as more adaptive learning methods, academic and moral balance, and a conducive learning environment. Further research is expected to explore the effectiveness of other methods in increasing the internalization of moral values ​​in the lives of female students.